(untitled) (Journal of the College of Basic Education, 2022)
This research is based on an effort to implement a proposed reading mechanism that we have been working on for a long time, its dimensions unfold in the circulation of the text and reading it several times and contemplating it, and listening to its utterances, leading to placing the hand on an adopted (dominant) that will present its revelations through the levels of the text: lexical, syntactic and rhythmic, up to What the reading ends with is an explanation of (the semantic text achiever), which becomes a monitoring of those caches whose curtains the reading revealed.